Gambaran Regulasi Emosi Pada Keluarga Yang Merawat Pasien Gangguan Jiwa Berat Di Rumah Sakit Jiwa Prof.dr. V.L Ratumbuysang Provinsi Sulawesi Utara - Tumbage, Meyfania Miracle Christy; Bidjuni, Hendro; Rumampuk, Jimmy (Mapalus Nursing Science Journal, 2025)
Background: emotional regulation in families caring for patients with mental disorders, there is a psychological impact on families who care for people with mental health problems (ODGJ) experience negative thoughts and emotions through thoughts and expressions or communication so that it can cause pressure when a caregiver/family has poor emotional management skills, it will add to problems that have an impact on patients and the caregiver itself. Objective: to find out the picture of emotional regulation in families who treat patients with mental disorders at the psychiatric hospital prof.dr. V.L ratumbuysang. Method: This study is a quantitative research with a descriptive research design involving 100 respondents.Data collection was carried out using the Emotion Regulation Questionnaire (ERQ) questionnaire from Gross and John (2003). Results: based on the characteristics of the respondents, it was found that most of the respondents were women (59%) and Respondents with Emotional Regulation